2014
DOI: 10.1136/archdischild-2013-304601
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of chronic viral hepatitis C in children and adolescents: UK experience

Abstract: Children respond well to therapy for CHC. Treatment was tolerated with minimal impact on QoL and no significant effect on growth. Knowledge of viral and IL28 genotypes and early viral response is useful to plan treatment in children and provide appropriate counselling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 36 publications
1
16
0
1
Order By: Relevance
“…[42] In particular, even if pain represents a constant concern among health professionals, strategies to reduce pain in HD patients still seem wanting. [42,43] In part this is due to organizational uncertainty about who, the nurse or the physician, is responsible for treating symptoms. [44] Further to these results, healthcare professionals should assess presence of pain in HD patients systematically and propose pharmacological and non-pharmacological solutions to remedy the situation.…”
Section: Discussionmentioning
confidence: 99%
“…[42] In particular, even if pain represents a constant concern among health professionals, strategies to reduce pain in HD patients still seem wanting. [42,43] In part this is due to organizational uncertainty about who, the nurse or the physician, is responsible for treating symptoms. [44] Further to these results, healthcare professionals should assess presence of pain in HD patients systematically and propose pharmacological and non-pharmacological solutions to remedy the situation.…”
Section: Discussionmentioning
confidence: 99%
“…The antiviral drug ribavirin has been used for treatment of hepatitis C virus (HCV) infection in combination with type I IFN (Abdel-Hady et al, 2014;Bansal et al, 2015). Ribavirin exerts its antiviral effect by inhibiting viral RNA-dependent RNA polymerases (Bougie and Bisaillon, 2003;Maag et al, 2001;Toltzis et al, 1988), inhibiting mRNA cap formation (Goswami et al, 1979), and upregulating genes related to IFN signaling (Feld et al, 2007;Zhang et al, 2003), as well as other mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on pediatric HCV-infected patients found 83% and 86.3% of SVR rate [11,12]. A recent study from UK found that 76% of pediatric patients with CHC who received Peg-IFN and RBV achieved SVR [13]. The reason for the higher SVR rate can be due to the minimal liver fibrosis in the children.…”
Section: Discussionmentioning
confidence: 96%